Predicting Target Genes of San-Huang-Chai-Zhu Formula in Treating ANIT-Induced Acute Intrahepatic Cholestasis Rat Model via Bioinformatics Analysis Combined with Experimental Validation. (2nd September 2021) - Yao, Jiaming; Yan, Junbin; Wu, Jinting; Yu, Jianshun; He, Beihui; Chen, Xi; Chen, Zhiyun
Abstract : Background . San-Huang-Chai-Zhu formula (SHCZF) has been used to improve cholestasis for many years. This study aims to predict the possible gene targets of SHCZF in treating acute intrahepatic cholestasis (AIC) in rats. Materials and Methods . Eighteen SD rats were randomly assigned to the normal group, ANIT group, and ANIT + SHCZF group. Alpha-naphthylisothiocyanate (ANIT) was used to induce AIC. Serum biochemical indexes were detected in each group. After treatment, the livers were collected and used to extract RNA. The library was constructed by TruSeq RNA, sequenced by Illumina, and analyzed by various bioinformatics methods. qRT-PCR was used to verify the target genes related to the efficacy of SHCZF. Results . Serum ALT, AST, ALP, and TBIL were significantly higher in the ANIT group than in the normal group. Serum ALT and AST levels in the ANIT + SHCZF group were substantially lower than those in the ANIT group. A total of 354 intersected genes were screened by expression level correlation and PCA analysis, GO and KEGG pathway enrichment analysis, and WGCNA and STEM analysis. Then, 4 overlapping genes were found by pathway/BP/gene network construction. SHCZF reversed the downregulation of expression of CYP4A1 and HACL1 and the upregulation of expression of DBI and F11R induced by ANIT. In addition, the qRT-PCR result showed that mRNA expression of CYP4A1, HACL1, and F11R genes in the liver was consistent with the prediction result of bioinformatics analysis. Conclusion . CYP4A1, HACL1, and F11R are genes related to the occurrence of ANIT-induced AIC in rats and may be considered as targets of SHCZF for the treatment of AIC.